« Théorie du genre » et controverses d’égalité en France - Husson, Anne-Charlotte (Romanica Silesiana)
« Théorie du genre » and Controversies about Equal Rights in France Focusing on debates held in France and concerning gay marriage, and on the use of the expression “théorie du genre,” this article examines anti-gender discourse outside academic spheres and its use serving to dismiss women’s claims for equal rights. “Théorie du genre” is shown to constitute a mistranslation of “gender theory,” with conceptual but also political consequences, as the rejection of the concept of gender is presented as an act of national resistance to the importation of a foreign and dangerous concept. Anti-gender discourse is described as an “ideological formation” (rennes 93), and the prominence of the expression “théorie du genre” in recent public debates is analyzed in order to bring to light its Catholic grounding, its main semantic and lexical features, and its polemical purpose. Key words: polemics, gender, enunciation, translation, equal rights, ideology.